(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the 7-day nutritional regimen after surgery in patients with gastrointestinal cancer at K Hospital in 2024. Subjects and methods: This is a prospective descriptive study with a sample size of 256 patients with gastrointestinal cancer who were indicated for surgery. Results: The energy intake gradually increased from postoperative day 2 (reaching 962.7 ± 357.5 kcal) to postoperative day 4 (reaching 1370.8 ± 310.8 kcal), then decreased on postoperative day 7 (reaching 1172.5 ± 283.0 kcal). The percentage of patients meeting the recommendation of > 70% of energy needs was highest on day 4.5, with a rate of 78.5%. However, by postoperative day 7, this rate dropped to 56.3%. For protein values, the percentage of patients in the first 7 days post-surgery met the protein recommendation with a threshold of > 1.2 g/kg/day according to ESPEN guidelines, ranging from 0% to 28.1%. Conclusion: The percentage of patients receiving adequate nutrition to meet energy and protein needs in the 7-day postoperative regimen is still low.